Islam dan Kolonialisme Inggris pra-Malaysia dan Singapura - Aprilidiani, Niken; Shafira Azzahra, Nur Dhea (Syams, 2023)
This study aims to analyze the relationship between Islam and British colonialism before thefounding of Malaysia and Singapore. The era of British colonialism in this region had asignificant impact on the development of the Islamic religion and Muslim society in the region.In this analysis, we look at the period of British colonialism from the 18th century to theearly 20th century, during which the British controlled areas such as the Malay Peninsulaand Singapore Island. The British adopted a different approach to Islam in Malaysia andSingapore. In Malaysia, the British used the existing traditional Islamic legal system, whilein Singapore, the British introduced a more secular British legal system. In the Malaysiancontext, British colonialism influenced the development of Islamic law and religiousinstitutions. The British introduced a more secular English legal system, which limited therole of Islamic law in public life. Despite this, Islam remained an important religion for theMuslim community in Singapore, and the British were not able to completely eradicate thereligion's influence. This research uses a historical approach and document analysis toinvestigate changes that occurred in religious practices and the influence of British colonialismon Islam before the founding of Malaysia and Singapore.